2000
DOI: 10.1055/s-2000-11534
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation and Segregation Analysis of Snoring and Symptoms of Obstructive Sleep Apnea

Abstract: To investigate possible modes of inheritance that would explain familial aggregation in obstructive sleep apnea (OSA), familial correlation and segregation analyses were performed on data derived from 584 pedigrees with 2019 cases enrolled in the Tucson Epidemiologic Study of Obstructive Airways Disease (TESOAD) who were at least 10 years of age and who had information pertaining to snoring and daytime sleepiness. Data were obtained from the 9th (May 1984 to October 1985) and 12th (February 1990 to October 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Segregation analyses for snoring with regressive familial effects and siblings, age and obesity covariates showed no evidence of Mendelian transmission. This study reported a significant increase of familial insomnia, warranting further genetic studies in primary insomnia with early age at onset 18 .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Segregation analyses for snoring with regressive familial effects and siblings, age and obesity covariates showed no evidence of Mendelian transmission. This study reported a significant increase of familial insomnia, warranting further genetic studies in primary insomnia with early age at onset 18 .…”
Section: Discussionmentioning
confidence: 56%
“…In the analysis of the TESOAD (Tuson epidemiologic study of obstructive airway disease) study by Holberg et al, familial correlations for snoring showed significant mother-child and sibling correlations but not father-child correlations 18 . For sleep apnea, significant parentdaughter but not parent-son or sibling correlations were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Holberg 9 . They focused on two phenomena: isolated snoring, and snoring associated with daytime somnolence as proxy for obstructive sleep apnea/ hypopnea syndrome (OSAHS).…”
Section: Functional Studiesmentioning
confidence: 99%
“…Twin studies have found greater concordance for snoring among monozygotic twins compared to dizygotic twins [16]. Familial aggregation and segregation analysis of snoring and symptoms of OSAHS applied to 584 pedigrees with 2 019 cases enrolled in the Tucson Epidemiologic Study of Obstructive Airways Disease demonstrated Mendelian dominant or co‐dominant transmission [17]. However, this analysis also found that a nongenetic model would fit the data equally well, suggesting that environmental factors probably contribute to the development of OSAHS.…”
Section: Is the Obstructive Sleep Apnoea–hypopnoea Syndrome Hereditary?mentioning
confidence: 99%